Struktur dan Fungsi Ramulo di Nagari Kampuang Padang Kecamatan Tigo Nagari Kabupaten Pasaman - Rozalina, Selvia; Hamidin, Hamidin; Amir, Amril (Universitas Negeri Padang, 2012)
The purposes of this study were to structure and function Kampuang ramulo in Nagari Padang District Tigo Pasaman. Ramulo object of this research is used by society to delivering the message of Islam in Sub Tigo Nagari Nagari Padang Kampuang Pasaman. This research is a qualitative study using descriptive methods. The data of this study is ramulo structure consisting of the physical structure and the inner structure and function ramulo consisting of religious functions, education, communication, social, and entertainment. The data source of this research is ramulo in Nagari Padang Kampuang taken from native speakers or informant who is a tuo kampuang and tutor in Kampuang Nagari Padang. Data collected through observation, interviews, and recording the results of structured interviews with informants. Based on interviews and observations gained as much as 15 milestones ramulo.